Odpowiedź:
1 i 1/2 *2/7 /2 i 1/4 *1/3= 3/2 *2/7 : ( 9/4*1/3)( skracamy 2 i 2 przez 2 ,oraz 3 i 9
przez 3)=3*1/7 : 3/4= 3/7 *4/3/( skracamy 3 i 3 przez 3)= 1/7*4= 4/7
d) 2/5 : 2 i 1/2 /3/7 *1 i 1/6= 2/5 : 5/2 /3/7 *7/6( skracamy w mianowniku
7 i 7 przez 7, oraz 3 i 6 przez 3)= 2/5* 2/5 / 1/2= 4/25 : 1/2= 4/25 *2=8/25
n) 3 i 3/11 : 3= 36/11 *1/3( skracamy 36 i 3 przez 3)= 12/11= 1 i 1/11
o) 2 i 3/7 : 4 i 6/7= 17/7 : 34/7= 17/7 * 7/34( skracamy 7 i 7 przez 7, oraz
17 i 34 przez 17)= 1/2
Szczegółowe wyjaśnienie: